COMMUNICATION: THE “MULTIPLIER COMPETENCY” FOR EXECUTIVE MANAGEMENT LEADERSHIP IN SOUTH AFRICAN UNIVERSITIES OF TECHNOLOGY: Received: 17th November 2025, Revised: 13th January 2026, 20th January 2026, Accepted: 2nd February 2026, Date of Publication: 31st March 2026 - Courtley Pharaoh (PEOPLE: International Journal of Social Sciences, 2026)
This study examines communication as a vital competency for executive management in South African universities of technology. Interviews with executives reveal that communication consistently amplifies other managerial skills, functioning as a multiplier competency across both routine and crisis contexts, and is therefore essential for effective higher education leadership. This exploratory study adopts a qualitative design, using semi-structured online interviews held through videoconferencing with 13 executive management members of UoTs. This approach provides a secure and flexible means of collecting real-time audio-visual perspectives from participants, closely resembling face-to-face interviews while maintaining compliance with COVID-19 safety measures. To examine management competencies in depth, the study applies Qualitative Content Analysis (QCA). Communication competency emerged as a core multiplier competency for executive management in universities of technology. In normal operations, it strengthens leadership, decision-making, negotiation, and accountability, while in crises, it reinforces risk management, problem-solving, emotional intelligence, and stakeholder reassurance. It is therefore indispensable for effective leadership across both stable and turbulent contexts. This study highlights communication as a pivotal “multiplier” competency for executive management in universities of technology, enhancing both routine and crisis leadership functions. Its dual-context impact—strengthening decision-making, accountability, and stakeholder engagement under normal operations, while supporting risk management and problem-solving during crises—offers novel insight. These findings underscore the strategic value of developing communication skills to reinforce multiple leadership competencies and promote resilient, adaptive management.